Effectiveness of Ultrasound-Guided Combined Sciatic-Femoral Nerve Block in Below Knee Surgery (Journal of Comilla Medical College Teachers' Association, 2026)
Background: Subarachnoid block (SAB) is commonly used for below-knee surgeries but is associated with haemodynamic instability and urinary retention. Ultrasound-guided combined sciatic-femoral nerve block (CSFNB) may provide a safer alternative. Meningitis, postdural puncture headache and spinal hematoma can be avoided by the use of peripheral nerve block technique.Objective: The aim of this study was to compare efficacy of combined sciatic and femoral nerve block with respect to haemodynamic parameters, onset and duration of the block and complications associated with it over conventional subarachnoid block.Methods: In this randomized controlled trial (October 2022–March 2024, Dhaka Medical College), 60 ASA I–II adults undergoing elective below-knee surgery were allocated to SAB (Group A, n=30) or CSFNB (Group B, n=30) by block random sampling method of 3, 1:1 design. Group A received 2.5 mL 0.5% hyperbaric bupivacaine with fentanyl; Group B received ultrasound- guided femoral and sciatic blocks with 0.25% bupivacaine plus 2% lignocaine with adrenaline. Haemodynamic changes, block onset/duration, analgesia duration, and adverse events were assessed.Results: Group A had faster onset of sensory (3.1±0.7 min) and motor block (6.7±0.4 min) compared with Group B (15.7±1.6 min and 23.4±1.3 min, p